HUBUNGAN PERILAKU MEROKOK DENGAN KEJADIAN TUBERKULOSIS PARU PADA PASIEN BALAI PENGOBATAN PENYAKIT PARU-PARU - Nova Arikhman (LLDIKTI Wilayah X, 2011)
The purpose of this research is to find out relationship of smoking behavior with the occurence of tuberculosis of lungs at the BP4 Lubuk Alung West Sumatera. The research is descriptive correlation by using cross-sectional approach. The research population consist of all patient who have tuberculosis totaling 845 patient, part of them are taken as research 272 respondent by simple random sampling. To collect data the researcher uses HPMKTB Paru questioners, statistical analysis used chi-square. The statistical analysis, indicates that there is significant the relationship of the smoking behavior with occurence tuberculosis of lungs. On the based of the research findings, it is recommended to BP4 Lubuk Alung, to increase the efforts of knowledge through healthy life, with pressing that smoking behavior is one of the effect faktors occur tuberculosis.